Development of a Bowtie Inversion Technique for Real‐Time Processing of the GOES‐16/‐17 SEISS MPS‐HI Electron Channels. Issue 4 (13th April 2020) - Boudouridis, A.; Rodriguez, J.V.; Kress, B.T.; Dichter, B.K.; Onsager, T.G.
Abstract: The Space Environment In‐Situ Suite on the Geostationary Operational Environmental Satellite (GOES)‐R series of satellites includes a new instrument for measuring radiation belt electrons and protons, the Magnetospheric Particle Sensor–High Energy (MPS‐HI). The MPS‐HI electron channels cover the energy range 50 keV to 4 MeV. The conversion of raw MPS‐HI electron telescope counts to fluxes is based on the so‐called bowtie technique. The goal of the bowtie analysis is to calculate for each energy channel an energy/geometric factor pair applicable to a wide range of energy spectra and for which the geometric factor error is minimized. Rather than using idealized analytical spectral functions, we use observed high‐resolution spectra from the cross‐calibrated Combined Release and Radiation Effects Satellite (CRRES) Medium Electron Sensor A and High Energy Electron Fluxmeter data set from the period 1990–1991, restricted to 6 < L < 8. One thousand randomly selected CRRES spectra are used to perform the bowtie analysis and determine the MPS‐HI channel energy/geometric factor characteristics. The results are used to convert the GOES‐16/‐17 MPS‐HI electron counts to fluxes. The same bowtie technique is used to calculate effective energies and geometric factors for the GOES‐13/‐14 Magnetospheric Electron Detector ME1‐ME5 (30–600 keV) electron channels. We compare the fluxes from the various spacecraft (GOES‐16/‐13, GOES‐17/‐14, and GOES‐16/‐17) over periods of several months to determine the applicability and utility of the bowtie analysis. Finally, we compare the GOES‐16/‐13 fluxes during 22 days of near conjunction. All comparisons show good agreement among the various satellite data sets. Key Points: Development of a bowtie technique for the calibration of the GOES‐R satellite series SEISS MPS‐HI electron data Cross‐satellite comparison of the electron data sets from various GOES satellites Comparison of the >2‐MeV electron channel (used for space weather alerts by SWPC) with the analogous channel from older instruments